Jewish Burial of Late Antiquity - Brunnlerhman, Joshua (Iggrot Ha’Ari, 2021)
What did Jewish burial in late Antiquity look like? In the Middle Ages, burial in plots of ground in cemeteries grew to become the prevalent method of burial and the method that is still dominant to this day. Yet, as we know from tradition, burial does not require the existence of cemeteries; afterall our ancestors in Tanach & Talmud were buried in caves and underground tombs. So what did Jewish burial look like in Late Antiquity, specifically between the Biblical and Temple times and the Medieval Era? The development of Jewish burial practices spanned the entire Jewish diaspora and it took centuries to take shape, but by looking at the archeological findings of late antique burials we can come to understand what it meant to have a Jewish burial in late antiquity.